Alice: Arts Lab in Interfaces, Computers, and Everything Else - Research report (2019) - Schiavoni, Flávio Luiz; Gomes, André; de Paulo, Avner; de Souza, Carlos; Carvalho, Fábio; Resende, Frederico; Rocha, Gabriel Lopes; Silva Junior, Igino; Andrade, Igor; Araújo, João; Santos, Luísa; Gonçalves, Luan; et al. (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2019: Anais do XVII Simpósio Brasileiro de Computação Musical, 2019)
Located in the Computer Science Department of the Federal University of São João del-Rei, but not limited to just this space, ALICE has emerged as a research group focused on the development of software, art and technologies for the area of computer music and digital arts. Over the time, ALICE became the laboratory to develop technologies to an artistic group, called Orchidea, focused on the creation of digital art, encompassing students from diverse areas, such as Computer Science, Scenic Arts, Architecture and Music in a transdisciplinary context of art creation. In this way, this work aims to present the various initiatives and proposals carried out by the ALICE, addressing the development of technological products, through the tools implemented and the external tools used for teaching and for artistic creation. In addition, this work describes the current researches that are under development by the members of the groups, also highlighting the development of the digital performance titled “O Chaos das 5” and all the aspects and learning that we have obtained so far with this performance.